The effect of business digitalization, technology utilization, and financial literacy on the sustainability of MSMEs in Surakarta - Muhammad Luthfi Hamdani; Naili Amalia (Review of Management, Accounting, and Business Studies, 2022)
Micro and Small Enterprises (MSMEs) constitute one of the business categories forming the backbone of the national economy, including in the city of Surakarta, Central Java. According to data from the Central Bureau of Statistics (BPS) in 2019, Surakarta had 1,863 micro and small business actors, employing 42,962 workers. The continuity of SMEs is anticipated to play a crucial role in strengthening the community's economy. Against this backdrop, this study aimed to analyze the impact of business digitalization, technology use, and financial literacy on the sustainability of SMEs in Surakarta. The research employed a quantitative approach, with data analysis conducted using multiple linear regression tests. The results revealed that the independent variables of business digitalization, technology use, and financial literacy each had a significant positive effect on business sustainability individually. Simultaneously, all three variables significantly influenced business sustainability. Based on these findings, it is recommended that future SMEs focus on enhancing their business digitalization, technology use, and understanding of financial literacy.